Facing disruptive technologies: aligning purchasing maturity to contingencies. Issue 1 (3rd December 2018) - Søgaard, Britta; Skipworth, Heather Dawn; Bourlakis, Michael; Mena, Carlos; Wilding, Richard
Abstract : Purpose: This paper aims to explore how purchasing could respond to disruptive technologies by examining the assumptions underlying purchasing strategic alignment and purchasing maturity through a contingency lens. Design/methodology/approach: This study uses a systematic review across purchasing maturity and purchasing strategic alignment literature. This is supplemented with exploratory case studies to include practitioners' views. Findings: This research demonstrates that neither purchasing maturity nor purchasing strategic alignment are suitable approaches to respond to disruptive technologies. Purchasing maturity does not allow purchasing managers to select relevant practices. It also shows no consideration of any contingencies, which practitioners highlight as important for the selection of practices. Purchasing strategic alignment includes the company strategy as a contingency but does not provide any practices to choose from. It does not include any other contextual contingencies considered important by practitioners. The findings indicate that linking the two research streams may provide a more suitable approach to responding to disruptive technologies. Research limitations/implications: This research demonstrates the requirement to develop a new approach to responding to disruptive technologies, by linking purchasing maturity and purchasing strategic alignment to contextual contingencies. This is a currently unexplored approach in academic literature, which refutes the generally accepted premise that higher maturity unilaterally supports a better positioning towards technological disruption. This research also highlights a requirement for practitioners to shift their approach to "best practices". Originality/value: This is the first research to systematically review the relationships between purchasing maturity and purchasing strategic alignment. It adds to contingency theory by suggesting that purchasing maturity models can support the achievement of strategic alignment. Also, future research directions are suggested to explore these relationships.